Improved Production and Physicochemical Stability of a Bioemulsifier from a Marine Acinetobacter beijerinckii PHCS 7 - Dharmadevi, Devaraj; Aravindan, Baskaran; Ganesh, Punamalai; Sivasubramani, Kandasamy (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The commercial use of bioemulsifiers on various fields still faces the hindrance mainly because of low productivity. Hence, the current study inclines to improve the synthesis of a bioemulsifier from a marine Acinetobacter beijerinckii PHCS 7, which was previously isolated from a sediment sample polluted with petroleum hydrocarbons and this study also reports on the stability of the extracted emulsifier. During the optimization of biotic and abiotic factors, the use of 1% of trehalose, 0.5% yeast extract, 0.5% coconut oil, 200 rpm agitation, 30 ppt salinity and 2% of inoculum size evidenced improved production of bioemulsifier. Large-scale emulsifier synthesis was carried out based on the optimised conditions, followed by diethyl ether extraction and the stability of the extracted bioemulsifier was characterized. The findings demonstrated that the extracted bioemulsifier was stable under wide range of extreme situations, including those involving temperature, pH, and salinity. The improved synthesis and physicochemical stability of a bioemulsifier from a marine A. beijerinckii PHCS 7 reveal the wide spectrum of its uses in both bioindustrial and environmental domains.